A Project for Oil-Rich Ecuador: The Nationalist Revolution of the Armed Forces - García Gallegos, Bertha J. (Revolutionary nationalism: The 1970s and the Contemporary History of Ecuador, 2026)
It examines the rise of the military as political actors amid the oil boom. In the face of the crisis of Velasco’s regime and the weakness of the political parties, an alliance between the Navy and technocrats devised a modernizing and anti-oligarchic project. The plan proposed agrarian, tax, and industrial reforms, using oil to strengthen the state. The 1972 coup established a “Revolutionary Government” that sought social redemption and national sovereignty.